PENGARUH PEMBELAJARAN DARING MATA PELAJARAN SEJARAH MELALUI MICROSOFT OFFICE 365 - Aziizah, Anisatul; Sakti, Tegar Bima; Andriyanto, Andriyanto (Keraton: Journal of History Education and Culture, 2020)
The purpose of this study is to describe how Microsoft Office 365 applications are used in online learning. This study uses a qualitative approach with a descriptive design. The data collection technique is done by collecting information and pictures. The data obtained were then described descriptively. From this method, the research results show that the use of Microsoft Office 365 in online learning activities is said to be quite effective and efficient. With various features in one application, it makes it easier for teachers to use them, because teachers can deliver teaching materials using various facilities or features provided by the office, not only in text but also in text. video form. In addition, teachers can also monitor the activeness of their students with the chat feature, and can efficiently assign assignments as evaluation materials to determine the level of student understanding. In addition, Office 365 can also be used for video conferencing for face-to-face learning via online. This shows that learning using Microsoft Office 365 has problems in terms of students regarding the problem of the size of the application and different network questions for each student but for questions about the Office 365 features it is good with complete teaching features. Keywords : Applications, Learning, Microsoft, Online